Outcomes of 23-Gauge Vitrectomy Combined with Phacoemulsification, Panretinal Photocoagulation, and Trabeculectomy without Use of Anti-VEGF Agents for Neovascular Glaucoma with Vitreous Hemorrhage - Hua Yan (Journal of Ophthalmology)
Purpose. To evaluate the outcomes of 23-gauge vitrectomy combined with phacoemulsification, PRP and trabeculectomy without use of anti-VEGF-agents for NVG. Methods. Eighteen eyes of 18 patients with NVG underwent 23-gauge vitrectomy combined with phacoemulsification, PRP and trabeculectomy without use of anti-VEGF agents. The preoperative BCVA ranged from light perception to 0.2. The preoperative IOP ranged from 38 mmHg to 64 mmHg with a mean of 54±8 mmHg. The average follow-up time was 14.5±3 months with a range from 11 to 24 months. Results. The postoperative VA increased in 14 eyes and was stable in 4 eyes at the final follow-up. The mean IOP was 12±3 mmHg at postoperative day 1. The mean IOP was 15±2 mmHg, 16±3 mmHg, 23±5 mmHg, 28±4 mmHg, 22±5 mmHg, 17±3 mmHg, and 19±4 mmHg at postoperative days 2 and 3, 1, 2, 3, and 12 weeks, and 1 year postoperatively, respectively, with a range from 10 to 30 mmHg at the final follow-up time point of one year. The IOP was significantly lower than the preoperative one 12 weeks postoperatively (p<0.05). Conclusion. 23-gauge vitrectomy combined with phacoemulsification, PRP, and trabeculectomy without use of anti-VEGF-agents is a safe and effective method in treating NVG.